Passive UHF tag collision resolution on PHY layer - Hai-feng WU; Yu ZENG (Tongxin xuebao)
An algorithm was proposed to separate the collided signals on the PHY layer.The proposed algorithm firstly adopts a dynamic-scale transformation to transform the collided signals to time-scale domains.And then,a transforming matrix would be obtained from the transformation.Finally,least square and minimum mean square error criterion are utilized to separate the collided tag signals.Simulation results show that,in contrast to the conventional signal separation approaches,the proposed algorithm can separate more than two tag signals under single-antenna condition and have better performance of separation even without capture effect.